DETERMINATION OF SOIL EROSION BY USLE USING REMOTE SENSING IN THE HILL KATHRYN MINING AREA PT VALE INDONESIA TBK. - Jamalullael, Bayu
their mining areas, including areas that were previously considered finished. Changes in land cover as a result of land clearing activities in the development of an area can affect the erosion rate of that area. Remote sensing technology can be used to detect changes in land cover more practically. This study aims to analyze changes in land erosion rates due to mining area development with the help of remote sensing technology for environmental management facility design considerations. The research area is Hill Kathryn, an area in the Sorowako Block of PT Vale Indonesia, which started mining again in 2016 since it was stopped in 2009. Satellite image data is used in the analysis of land cover changes in the range of 2015 - 2023. Along with supporting data in the form of annual rainfall data, soil type and topography, this data is then used to estimate erosion rates using the USLE method. The research results show that the remote sensing method is quite effective in detecting changes in land cover. As mining progresses, the area of land divided based on vegetation cover (forest and grass, mined area) changes according to the characteristics of mining activities. Areas with the forest category decrease due to land clearing into mining work areas so that the mined area increases. Changes also occur in the length and slope of the slope which increases because it changes into a mining work area. Changes in land conditions during this period resulted in erosion rate classifications in the forest area (including long-reclaimed areas) between very light - light while the grass area (including new reclamation areas) between light - medium and for mined areas between medium - heavy. The highest erosion rate occurred in 2021 then decreased until 2023. The calculation of the sediment load balance that must be managed, which is calculated based on the results of estimating the total erosion volume in that period and the sediment capacity in the sedimentation pond, shows that not all eroded sediment volumes are carried to the sediment pond because it has been deposited in the flat surface flow area upstream of the sedimentation pond.